Action of anti-M3 muscarinic acetylcholine receptor IgG of primary Sjögren's syndrome on the enzymatic antioxidant system in rat submandibular gland - Reina, Silvia Lorena (2015)
BACKGROUND: We demonstrate that serum immunoglobulin G (IgG) directed against glandular M3 muscarinic acetylcholine receptors (M₃mAChR) and pilocarpine triggers the increment of superoxide dismutase (SOD) and catalase (CAT) and the production of nitric oxide (NO) and prostaglandin E₂(PGE₂). METHODS: Enzyme-linked immunosorbent assay (ELISA) was performed in the presence of the human M₂mAChR synthetic peptide as antigen to detect in serum of pSS patients the autoantibodies. Further, SOD and CAT specific activity and NO were determined chemically in the presence of anti-M₃mAChR IgG and pilocarpine. The level of PGE₂generation in the presence of autoantibody and pilocarpine was determined by ELISA. RESULTS: An association between anti-M₂mAChR autoantibodies and pilocarpine given the increment of the specific activity of SOD and CAT in the serum of pSS patients and in the rat submandibular gland was observed. As a result of this action, M₃synthetic peptide and atropine abrogated the stimulatory action. The L-type calcium channel, calcium/calmodulin complex and COX-2 inhibitors selectively blocked the increment of the specific activity of SOD and CAT in the rat submandibular gland. An increased production of NO and PGE₂by the cholinergic autoantibody and pilocarpine was also detected. CONCLUSION: On the basis of these results, the increment of the specific activity of SOD and CAT in pSS patients as compared to control healthy individuals may be seen as a defensive reaction to the increment of the amount of ROS, which becoming uncontrollable, leads to irreversible cellular and tissue damage.